THE ROLE AND IMPACT OF INFORMATION TECHNOLOGY IN THE DEVELOPMENT OF TOURISM AND HOTEL BUSINESS - Khasanova Nargiza Athamovna; Turdiqulova Safina Akhtamovna (Western European Studies, 2024)
In the field of tourism, information technology is an important tool for direct business development and creation of modern jobs. And in the management of the tourism sector, information technology is the basis for obtaining reliable information and making decisions based on it by processing various forms of primary data in order to achieve optimal results in the tourism business with the help of hardware and software tools. We have studied such aspects of tourism in this article.
Keywords: Tourist; tour operator; travel agent